Environmental impacts of the Covid-19 pandemic on the world and Iran - Mohammad Yazdi (Sustainable Earth Trends)
The coronavirus disease or the so-called Covid-19 is a highly transmittable and pathogenic viral infection which emerged in Wuhan, China and spread rapidly around the world. The virus has resulted in about 4.2 million infections and 280,000 deaths (as of 10 May, 2020). Covid-19 is affecting not only health, economy, culture and life style but also it is going to affect the ecosystems and environment of the world. The ideas about role of this crisis in ecosystem and environment are quite different. Optimists believe that this crisis is the best opportunity to reduce pressure on natural resources and provides time for self-reconstruction of the ecosystems and environment. The pessimist, on the other hand, state that the positive effects of Covid-19 on the environment is not much and would diminish soon, and the earth is hurtling towards a catastrophe worse than the dinosaur extinction. The most positive impacts of this crisis are reduced pressure on natural resources, decreasing in air pollution and climate change, deeper understanding of the ecosystems and environment saving. The significant negative impacts of this crisis are human infection and death, billions USD in economic losses, increasing in household consumption, medicine, faces masks and medical gloves and challenge for burial of household and medical waste, reduction in environmental diplomacy, reduction in accuracy of weather forecasts and treat for wildlife infection. Iran is the home to the second most infected and recovered cases (up to 75%) after China. Several impacts have been reported on the human and natural environment of Iran. The virus has resulted in about 108,000 infections and 6,700 deaths (as of 10 May, 2020). In response to coronavirus, the government cancelled public events such as Friday prayers, festival celebrations, and sporting events, as well as closed schools, universities, shopping centers, bazaars, and even holy shrines. Consequently, the spread of infection is relatively controlled from over 200 to about 40 deaths per day. The impacts on the ecosystems and environment of Iran are similar to that reported in other parts of the world.